Embracing chaos: the unpredictability of animated logos shapes users’ sustained attention - Guan, Wen; Cho, Dong Min; Zheng, Li (Frontiers in Psychology, 2025)
IntroductionAnimated logos have become a substantial investment in brand marketing, and designers tend to use flashy presentation effects for brand animations. Brands must understand how effectively animated logos capture users’ attention in media communication of visual distractions. However, the reasons for the impact on users’ sustained attention are not yet clear. By investigating users’ perceptions of animated brand logos, this study proposes a new dimension: “perceived unpredictability.”MethodsCombining previous studies on physics, psychology, and marketing, we analyze 63 actual cases and demonstrate an inverted U-shaped relationship between perceived unpredictability and sustained attention. Study 1 conducted a moderated mediation analysis using 1,844 questionnaires.ResultsThere exists a significant mediating effect through users’ perceived novelty, while brand type acts as a moderator in this process. Specifically, animated logos with unpredictable features in feel brands with hedonic emotional appeals enhance users’ sustained attention, while the opposite is true for think brands with utilitarian cognitive appeals. To avoid confounding effects of actual cases, Study 2 partially replicated the findings regarding the effect of perceived unpredictability on sustained attention under more demanding conditions using eye-tracking, further confirming the robustness of the results.DiscussionOur study provides new evidence for mechanisms by which animated logos affect sustained attention through self-report and behavioral measures and reveals which brands can benefit from animated logos with unpredictable characteristics. These findings provide feasible suggestions for marketers and designers to enhance brand influence.